Newsletter No. 17 - (:unkn) unknown (My University, 2007)
Information about the forthcoming LSAC Research Conference, Wave 2 data, Wave 2.5 and Wave 3 is in this edition of the Growing Up in Australia newsletter, as well as Life at 3 production and the Life at 2 website, and details of publications using Growing Up in Australia data.
17
Newsletter
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology